Optimalisasi Pembelajaran PJOK SMK melalui Sinergi Deep Learning dan Project-Based Learning: Dampak terhadap Keterlibatan Multidimensional dan Kemandirian Belajar Siswa - Farid M Alhumary; Benny Aprial. M; I Gede Angga Andika; Dedi Nofrizal; Joko Priono; Joka Novetra; Dewi Ayu Lestari; Rizki Kurniati; Ignasius Ivan Kurnia Ndruru; Yuspiter Laia; Lukman Nasution (Jurnal Inovasi Olahraga, 2026)
The 21st-century learning paradigm demands the transformation of physical education pedagogy from teacher-centered to constructivist approaches that facilitate meaningful learning. This paper aims to optimize vocational physical education through the integration of Deep Learning based on Project-Based Learning (PjBL) to enhance student engagement and self-regulated learning. The community service activity employed an educative-participatory approach involving five teachers and 120 students at SMK Negeri 14 Medan. The stages included initial assessment, conceptual training, implementation workshops, and comprehensive evaluation. Instruments comprised pedagogical understanding tests, Student Engagement questionnaires, Self-Regulated Learning scales, FGDs, and classroom observations. Results indicated significant improvements in teachers' conceptual understanding (N-Gain 0.69; p<0.05), student engagement across cognitive (+39.2%), behavioral (+42.5%), and emotional (+35.8%) dimensions, and self-regulated learning (N-Gain 0.53). The Deep-PjBL integration effectively transformed conventional physical education into meaningful learning that develops higher-order thinking skills and health literacy among vocational students. The establishment of the "Geriak PJOK Medan" Community of Practice ensures the sustainability of pedagogical innovation post-intervention.